The Benefits of Bilingualism (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
More and more people are becoming bilingual and it is worth the time and effort to learn a different language. Spanning from neurological to academic and beyond, research suggests that being bilingual has many benefits, including a sense of community and accomplishment. Research has shown that bilingualism at an early age has neurological and academic benefits.  Neurological benefits include plasticity of the brain, increase in brain activity, and a cognitive advantage. Academic benefits include a larger capacity for short term memory and a literacy advantage. The earlier a language is learned, the earlier it is obtained, and learning another language has lasting effects that can carry on to a child’s later education and life.            Keywords: benefits, bilingualism